Length of stay in health facilities after childbirth and associated maternal and neonatal factors in Ethiopia: a cross-sectional study from a national survey - Yemisrach Belete Biru; Getasew Assefa Lemelem; Nahom Solomon (BMJ Open)
Objective This study aimed to assess the length of stay in health facilities after childbirth and associated maternal and neonatal factors in Ethiopia.Design A cross-sectional study.Setting Ethiopia.Participants 2260 mothers who participated in the 2016 Ethiopian Demographic and Health Survey were included in the study.Outcome Length of stay in health facilities after childbirth was the outcome variable of the study.Result In Ethiopia, the mean duration of postpartum stay for mothers in health facilities was 21.96 (19.97–23.94) hours. Nine hundred and sixty-eight (34.80%) women remained in health institutions for ≥24 hours after delivery. Gestational age, birth weight and mode of delivery were significantly associated with length of stay. Gestational age was found to be inversely associated with length of stay. Mothers who had a vaginal delivery were 8.89% (adjusted HR (AHR) 8.89, 95% CI (4.28 to 18.46), p<0.001) more likely to discharge earlier from health facilities after delivery, compared with those who had a caesarian section. Women with larger size neonates during birth were 19% (AHR=0.81, 95% CI (0.67 to 0.96), p=0.019) more likely to stay longer in health facilities than women with average size neonates. Women with a smaller size neonate during birth were 16% (AHR=0.84, 95% CI (0.70 to 0.99), p=0.040) more likely to stay longer at a health facility, compared with those with an average size neonate.Conclusion A small percentage of Ethiopian mothers stayed in health facilities for 24 hours or more after delivery. Encouraging mothers to stay in health facilities for the recommended period after childbirth can play a significant role in reducing maternal and neonatal deaths.